PROJECT AND PORTFOLIO MANAGEMENT TOOLS SELECTION: Case study from the telecom sector - Aramja, Adil (My University, 2010)
Companies that are concerned about their sustainability in the market are entitled for a continuous product and service innovation task. New product and service development is not an easy one. As such it requires careful planning, organization and most of all financial and human resources commitment. Resources are very limited. Therefore, resources spending should be planned based on the corporate vision and strategy. Resources control should be established in the project level and also the portfolio level. Via resource control, company management can decide which projects can be accelerated, put on hold or stopped. This is what portfolio management is about. The use of information technology softwares in this field would be indeed of a great help for decision makers to take such decisions efficiently. The purpose of this thesis is to shed some light on how companies could manage their new product projects and portfolio via project and portfolio management tools. Through the case study, from the telecom sector, we are going to describe how companies are implementing their new product processes and portfolio management practices; moreover we are going to see how a company could choose an appropriate PPM tool. Finally, a shortlist of the different PPM tools that may satisfy the company needs in terms of project and portfolio management practices is presented.
Keywords: stage-gate model; new product development; portfolio management; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|